2015
DOI: 10.1111/tbj.12445
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Oncotype Dx Testing in Invasive Lobular Carcinoma?

Abstract: Oncotype Dx Breast Cancer Assay is a 21-gene assay used in estrogen receptor (ER)-positive breast cancer to predict benefit from chemotherapy (CT). Tumors are placed into one of three risk categories based on their recurrence score (RS). This paper explores the impact of tumor histopathologic features and Oncotype Dx RS on the treatment plan for invasive lobular carcinoma (ILC). Invasive lobular carcinoma cases submitted for Oncotype Dx testing were identified from a clinical data base. The histopathologic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…3,5,7 Histologic subtype is known to affect prognosis but it is not taken into account when patients are considered for Oncotype Dx testing. [8][9][10] Bomeisl et al demonstrated that "good prognosis" histologic subtype together with ER, PR, HER2, and lymph node status could be used for assessing risk in the absence of Oncotype Dx testing. 8 (Table S1) but did not diminish the predictive power of histologic subtype and grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,7 Histologic subtype is known to affect prognosis but it is not taken into account when patients are considered for Oncotype Dx testing. [8][9][10] Bomeisl et al demonstrated that "good prognosis" histologic subtype together with ER, PR, HER2, and lymph node status could be used for assessing risk in the absence of Oncotype Dx testing. 8 (Table S1) but did not diminish the predictive power of histologic subtype and grade.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a relationship between ORS and traditional prognostic markers like histologic grade, tumor size, hormone receptor status, lymph node status, and Ki-67 proliferation index. [3][4][5][6][7][8][9][10] In this study, we investigate whether certain histologic subtypes can be identified that may not benefit from OncotypeDx ® testing. Invasive carcinomas were graded according to the Elston and Ellis modification of the Nottingham grading system based on the extent of tubule formation, nuclear grade, and mitotic count (grade I: total score 3-5, grade II total score 6 or 7, and grade III total score 8 or 9).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to IDCs, approximately 40% of ILCs have an intermediate RS. Of relevance, Conlon and colleagues showed that in pleomorphic ILC cases, the proportion of tumors with intermediate RS may even be higher compared with classical ILC (69 × 32%, respectively) [Conlon et al 2015]. Until the results of prospective trials (such as the MINDACT or TAILORx trial) are available, the optimal management of the intermediate RS group remains unestablished.…”
Section: Chemotherapy Benefitmentioning
confidence: 99%
“…The genomic profile of ILCs is also different from that of ER‐positive/HER2 negative IDCs. The 21‐gene recurrence scores (RS) for ILCs are rarely categorized as high risk, whereas approximately 8% to 15% of ER‐positive/HER2‐negative IDCs are categorized as high risk . In addition, the pathologic complete response (pCR) rates after neoadjuvant chemotherapy are substantially lower for ILC compared with ER‐positive/HER2‐negative IDC .…”
Section: Introductionmentioning
confidence: 99%
“…The 21-gene recurrence scores (RS) for ILCs are rarely categorized as high risk, whereas approximately 8% to 15% of ER-positive/HER2-negative IDCs are categorized as high risk. [4][5][6] In addition, the pathologic complete response (pCR) rates after neoadjuvant chemotherapy are substantially lower for ILC compared with ER-positive/HER2-negative IDC. [7][8][9][10][11] Also, the relative effectiveness of letrozole compared with tamoxifen is higher for ILC versus IDC.…”
Section: Introductionmentioning
confidence: 99%